Working Group discussion three: elephant-habitat working group [African Elephant Specialist Group meeting, 17-22 November 1992, Victoria Falls, Zimbabwe] - Russell Taylor (Pachyderm)
Human influence poses the most fundamental threat to change manifested by ecosystem transformation, or habitat modification in which elephants may play a direct or indirect role. Outlines discussion related to both the management of elephants in protected areas, and the problems of management outside such areas as well as aspects of monitoring the impact of elephants on their habitats.